2007
DOI: 10.1007/s00438-006-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

The CBF gene family in hexaploid wheat and its relationship to the phylogenetic complexity of cereal CBFs

Abstract: Most temperate plants tolerate both chilling and freezing temperatures whereas many species from tropical regions suVer chilling injury when exposed to temperatures slightly above freezing. Cold acclimation induces the expression of cold-regulated genes needed to protect plants against freezing stress. This induction is mediated, in part, by the CBF transcription factor family. To understand the evolution and function of this family in cereals, we identiWed and characterized 15 diVerent CBF genes from hexaploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(195 citation statements)
references
References 54 publications
9
177
0
2
Order By: Relevance
“…Whereas Arabidopsis has three CBF genes present as a tandem cluster, wheat and other members of the Pooideae family have undergone a large expansion of this gene family, with eleven genes at the Fr-2 locus, eight of which are Pooideae-specific (Badawi et al 2007;Miller et al 2006;Skinner et al 2005). This expansion has been dated to coincide with a period of global cooling during the Eocene-Oligocene transition approximately 33 MYA (Sandve and Fjellheim 2010) and it has been proposed that the increase in the number of CBF genes and diversity at this locus may have occurred as a result of selection pressure for improved frost tolerance by this period of lower temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Arabidopsis has three CBF genes present as a tandem cluster, wheat and other members of the Pooideae family have undergone a large expansion of this gene family, with eleven genes at the Fr-2 locus, eight of which are Pooideae-specific (Badawi et al 2007;Miller et al 2006;Skinner et al 2005). This expansion has been dated to coincide with a period of global cooling during the Eocene-Oligocene transition approximately 33 MYA (Sandve and Fjellheim 2010) and it has been proposed that the increase in the number of CBF genes and diversity at this locus may have occurred as a result of selection pressure for improved frost tolerance by this period of lower temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In hexaploid wheat, for example, there are at least 15 CBF genes in each of the three wheat genomes, including eleven at each of the three Fr-2 loci (Badawi et al 2007). In barley, variation in CBF copy number was found at the Fr-H2 locus and this variation was associated with differences in freezing tolerance ).…”
Section: Introductionmentioning
confidence: 99%
“…However, while three closely related CBF genes have been reported in Arabidopsis, wheat and some other cereals have undertaken an extension in this family (Pearce et al 2013). Badawi et al (2007) reported that there are at least 15 CBF genes in each of the three hexaploid wheat genomes.…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…The barley genome harbors more than 20 CBF coding sequences in a single genotype (Skinner et al 2005). At least 13 of these colocalize in a cluster on the long arm of chromosome 5 (Skinner et al 2005(Skinner et al , 2006Miller et al 2006;Badawi et al 2007;Francia et al 2007;Knox et al 2010). These CBFs are grouped into two phylogenetic subgroups-HvCBF3/ CBFIII and HvCBF4/CBFIV, both of which are unique to the grasses (Skinner et al 2005;Badawi et al 2007).…”
Section: Introductionmentioning
confidence: 99%